The haploinsufficient Col3a1 mouse as a model for vascular Ehlers-Danlos syndrome - Cooper, Timothy K.; Zhong, Q.; Krawczyk, M.; Tae, H.-J.; Müller, G. A.; Schubert, Rudolf; Myers, L. A.; Dietz, H. C.; Talan, M. I.; Briest, W. (Veterinary pathology, 2010)
Vascular Ehlers-Danlos syndrome is a rare genetic disorder resulting from mutations in the α-1 chain of type III collagen (COL3A1) and manifesting as tissue fragility with spontaneous rupture of the bowel, gravid uterus, or large or medium arteries. The heterozygous Col3a1 knockout mouse was investigated as a model for this disease. The collagen content in the abdominal aorta of heterozygotes was reduced, and functional testing revealed diminishing wall strength of the aorta in these mice. Colons were grossly and histologically normal, but reduced strength and increased compliance of the wall were found in heterozygotes via pressure testing. Although mice demonstrated no life-threatening clinical signs or gross lesions of vascular subtype Ehlers-Danlos syndrome type IV, thorough histological examination of the aorta of heterozygous mice revealed the presence of a spectrum of lesions similar to those observed in human patients. Lesions increased in number and severity with age (0/5 [0%] in 2-month-old males vs 9/9 [100%] in 14-month-old males, P < .05) and were more common in male than female mice (23/26 [88.5%] vs 14/30 [46.7%] in 9- to 21-month-old animals, P < .05). Haploinsufficiency for Col3a1 in mice recapitulates features of vascular Ehlers-Danlos syndrome in humans and can be used as an experimental model.